Alendronate prevents glucocorticoid-induced osteoporosis in patients with rheumatic diseases: A meta-analysis. Issue 25 (June 2016) - Kan, Shun-Li; Yuan, Zhi-Fang; Li, Yan; Ai, Jie; Xu, Hong; Sun, Jing-Cheng; Feng, Shi-Qing
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Glucocorticoid-induced osteoporosis (GIOP) is a serious problem for patients with rheumatic diseases requiring long-term glucocorticoid treatment. Alendronate, a bisphosphonate, has been recommended in the prevention of GIOP. However, the efficacy and safety of alendronate in preventing GIOP remains controversial. We performed a meta-analysis to investigate the efficacy and safety of alendronate in preventing GIOP in patients with rheumatic diseases. We retrieved randomized controlled trials from PubMed, EMBASE, and the Cochrane Library. Two reviewers extracted the data and evaluated the risk of bias and quality of the evidence. We calculated the risk ratio (RR) with a 95% confidence interval (CI) for dichotomous outcomes, and the mean difference (MD) with a 95% CI for continuous outcomes using Review Manager, version 5.3. A total of 339 studies were found, and 9 studies (1134 patients) were included. Alendronate was not able to reduce the incidence of vertebral fractures (RR = 0.63, 95% CI: 0.10–4.04, P = 0.62) and nonvertebral fractures (RR = 0.40, 95% CI: 0.15–1.12, P = 0.08). Alendronate significantly increased the percent change in bone mineral density (BMD) at the lumbar spine (MD = 3.66, 95% CI: 2.58–4.74, P < 0.05), total hip (MD = 2.08, 95% CI: 0.41–3.74, P < 0.05), and trochanter (MD = 1.68, 95% CI: 0.75–2.61, P < 0.05). Significant differences were not observed in the percent change in BMD at the femoral neck (MD = −0.33, 95% CI: −2.79 to 2.13, P = 0.79) and total body (MD = 0.64, 95% CI: −0.06 to 1.34, P = 0.07). No significant differences in the adverse events were observed in patients treated with alendronate versus the controls (RR = 1.00, 95% CI: 0.94–1.07, P = 0.89). The odds of gastrointestinal adverse events were significantly reduced (RR = 0.77, 95% CI: 0.62–0.97, P < 0.05). Our analysis suggests that alendronate can increase the percent change in BMD at the lumbar spine, total hip, and trochanter, and is not associated with an increased incidence of gastrointestinal adverse events; however, the vertebral and nonvertebral fractures cannot be reduced. However, the results should be interpreted with caution due to the poor statistical power.